VALUE-ORIENTED HUMAN RESOURCE MANAGEMENT: SUSTAINABLE LOYALTY IN EDUCATIONAL ORGANIZATIONS - Iman Subasman; Bambang Firmansyah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Low employee loyalty and value internalization are still important issues in human resource management. Human resource value is a crucial factor in creating a good working climate. This study aims to analyze how value-oriented HR management shapes sustainable loyalty in the context of educational organizations. The approach used is qualitative, with data collection techniques through in-depth interviews, observation, and documentation studies in 17 secondary schools in West Java Province. The main findings show that employee loyalty is formed through a synergy between internalisation of organisational values, exemplary leadership, a comfortable working atmosphere, and a strong organisational culture. Values such as honesty, responsibility and sincerity drive employees' emotional attachment, which is strengthened by a supportive work climate and fair leadership. It was concluded that values-based HRM supports institutional stability and creates loyalty that grows naturally and sustainably. The results are useful for managers of educational institutions to design value-oriented HR development strategies, as well as build organizational culture